2011
DOI: 10.4088/jcp.10m06438
|View full text |Cite
|
Sign up to set email alerts
|

An International Consensus Study of Neuroleptic Malignant Syndrome Diagnostic Criteria Using the Delphi Method

Abstract: These diagnostic criteria significantly advance the field because they represent the consensus of an international multispecialty expert panel, include critical values, provide guidance regarding the relative importance of individual elements, and are less influenced by particular theoretical biases than most previously published criteria. They require validation before being applied in clinical settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
130
1
11

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(142 citation statements)
references
References 16 publications
0
130
1
11
Order By: Relevance
“…Although many clinical definitions of NMS have been proposed, a recent international consensus study of NMS experts has proposed the definition shown in Table 2 (8). These guidelines confirm that NMS remains a clinical diagnosis.…”
Section: What Key Findings Lead To the Diagnosis?mentioning
confidence: 89%
“…Although many clinical definitions of NMS have been proposed, a recent international consensus study of NMS experts has proposed the definition shown in Table 2 (8). These guidelines confirm that NMS remains a clinical diagnosis.…”
Section: What Key Findings Lead To the Diagnosis?mentioning
confidence: 89%
“…Often these patients are identified by neurology consultants who are called to evaluate a patient in the emergency room or on the wards with fever and change in mental status. Recent diagnostic criteria have been published, and most patients have fever, rigidity, change in mental status, autonomic instability, and an elevated creatinine kinase [17]. All drugs with dopamine-blocking activity have been reported to induce the syndrome, and it can occur in individuals without any underlying psychiatric or neurologic disorder.…”
Section: Neuroleptic Malignant Syndromementioning
confidence: 99%
“…Some cases show bradycardia [53,54] and bronchorrhea [55], indicative of strong vagal activity. Autonomic dysfunction is the hallmark of malignant catatonia [52,56], its drug-induced variant Neuroleptic Malignant Syndrome [57], and aseptic encephalitis with catatonic symptoms, including the recently coined anti-NMDAR encephalitis [58][59][60]. Early studies support that there is autonomic dysfunction in catatonia [61,62] but recent studies are lacking.…”
Section: Autonomic Dysfunction In Catatoniamentioning
confidence: 99%